Second harmonic generation contrasts of ferroelectric domain structures and composition in lithium niobate–tantalate mixed crystals - Koppitz, Boris; Saxena, Tanya; Bernhardt, Felix; Ganschow, Steffen; Sanna, Simone; Rüsing, Michael; Eng, Lukas M. (Journal of Applied Physics)
Lithium niobate–tantalate mixed (LNT) crystals promise improved performance and new applications for optical, piezomechanical, or electrical devices when compared to the end composition compounds lithium niobate and lithium tantalate. The macroscopic properties of ferroelectrics highly depend on the structure of the underlying ferroelectric domains, which within mixed crystals can interact with the local changes in chemical compositions. In this work, we demonstrate how ferroelectric domain walls can unambiguously be identified and distinguished from local changes in composition by correlating piezoresponse force microscopy with second harmonic generation microscopy, using the Cherenkov contrast, reference crystal contrast, and negative phase mismatching contrast. We demonstrate how measuring the associated intensity change when approaching negative phase mismatching can be used to deduce the local tantalum concentration fast and over a large sample area. Based on these results, we study the natural domain structures that appear from Czochralski-grown, multi-domain LNT solid solution crystals. The developed results and methods serve as the central foundation to poling these mixed crystal systems and are key for their integration and applications.